# Homomorphisms between $Z_n$ and $Z_m$ [closed]

Lets look at f: $Z_{10}$ to $Z_{12}$ . How do you prove that f is uniquely determined by what f is? What is the order of f?

## closed as off-topic by user26857, Namaste, Daniel W. Farlow, Zaid Alyafeai, C. FalconDec 27 '16 at 0:02

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – user26857, Namaste, Daniel W. Farlow, Zaid Alyafeai, C. Falcon
If this question can be reworded to fit the rules in the help center, please edit the question.

• For any group $G$, if $G$ is generated by set $X$, $G=\langle X\rangle$, and $f,g\colon G\to K$ are two group homomorphisms, then $f=g$ if and only if $f(x)=g(x)$ for all $x\in X$. – Arturo Magidin Oct 21 '11 at 18:48

Hint: Because $f$ is a homomorphism, $$f(n+m)=f(n)+f(m)$$ Use this to determine $f(n)$ in terms of $f(1)$, for any $n\in Z_{10}$.
Also, recall the definition of the order of an element of a group. The order of $f(1)$ is just its order as an element of $Z_{12}$. Consider: can we choose any element of $Z_{12}$ to be $f(1)$? Note that $$\underbrace{f(1)+\cdots+f(1)}_{10\text{ times}}=f(10)=f(0)=0\in Z_{12}$$ because $10=0$ in $Z_{10}$ and $f(0)=0$ because $f$ is a homomorpism.
Since each of these groups are cyclic, with generator $$, it will determine the rest. So, if $[m]\in\mathbb{Z}/10$ we have that $[m]=++\cdots +$ where $$ is added $m$ times. Then
$$f([m])=f(+\cdots +)=f()+\cdots +f(),$$
since $f$ is a homomorphism. But we know what $f()$ is and so $f([m])$ is determined. The order of $f()$ is the order of whatever element $$ gets mapped to.
In addition the other answers, note that both $n$ and $m$ constrain the order of $f()$ because $0 = f() = f(n \cdot ) = n \cdot f()$. Since we also have $0 = m \cdot f()$, we get $0 = \gcd(m,n) \cdot f()$. This gives an upper bound to the order of $f()$.